Investigating the Effects of Embodiment on Emotional Categorization of Faces and Words in Children and Adults - Vesker, Michael; Bahn, Daniela; Kauschke, Christina; Neumann, Mareike; Sweitzer, Cecilia; Schwarzer, Gudrun (Frontiers in Psychology, 2020)
The facial-feedback hypothesis indicates that besides being involved in the production of facial expressions, the musculature of the face also influences one’s perception of emotional stimuli. Recently, this effect has been the focus of increased scrutiny as efforts to replicate a key study with adult participants supporting this hypothesis using the so-called “pen-in-the-mouth” task have not been successful at several labs. Our series of experiments attempted to investigate whether the assumed embodiment effect can be reproduced in a simplified emotional categorization task for emotional faces and words. We also wanted to test whether the embodiment effect can be detected in children because it is assumed that their bodily processes are especially closely linked with their sensory and cognitive processes. Our experiments involved child and adult participants categorizing faces and words as positive or negative as quickly as possible, while inducing a positive or negative facial or bodily state (holding a straw in the mouth such that a smile or a frown was generated, or creating a positive or negative body posture). The positive or negative facial and bodily states could therefore be either congruent or incongruent with the valence of the target face and word stimuli. Our results did not show any significant differences between the congruent and incongruent conditions in either children or adults. This suggests that embodiment effects either do not significantly impact valence-based categorization, or are not strong enough to be detected by our approach considering the sample size in the present study.